2020
DOI: 10.1111/jce.14770
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and mortality associated with atrial arrhythmias among patients hospitalized with COVID‐19

Abstract: Introduction The impact of atrial arrhythmias on coronavirus disease 2019 (COVID‐19)‐associated outcomes are unclear. We sought to identify prevalence, risk factors and outcomes associated with atrial arrhythmias among patients hospitalized with COVID‐19. Methods An observational cohort study of 1053 patients with severe acute respiratory syndrome coronavirus 2 infection admitted to a quaternary care hospital and a community hospital was conducted. Data from electrocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 14 publications
6
97
3
4
Order By: Relevance
“…In a recent study of 700 hospitalized patients, 25 (3.6%) individuals were diagnosed with new onset AF 9 . In a larger population of patients from New York City, AA was also detected in 15.8% of the patients, 9.6% of which were newly diagnosed 10 . This rate is higher than the current study and it is possibly due to the higher percentage of white patients in their cohort.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study of 700 hospitalized patients, 25 (3.6%) individuals were diagnosed with new onset AF 9 . In a larger population of patients from New York City, AA was also detected in 15.8% of the patients, 9.6% of which were newly diagnosed 10 . This rate is higher than the current study and it is possibly due to the higher percentage of white patients in their cohort.…”
Section: Discussionmentioning
confidence: 92%
“…Nine hundred and sixteen potentially relevant studies were screened according to the inclusion and exclusion criteria. Finally, 23 studies with 108,745 COVID-19 patients 1 , 2 , 3 , 4 , 5 , 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 were eligibly included in the present quantitative meta-analysis. The study characteristics are summarized in Table 1 .…”
mentioning
confidence: 99%
“…However, the conclusions drawn from previous studies are not consistent. For instance, some studies observed that AF was significantly associated with an increased risk of mortality among COVID-19 patients, [1][2][3] while several other studies reported opposite results that there was no significant relation between AF and unfavorable outcomes of COVID-19 patients. [4][5][6] Several confounding factors such as gender, age and pre-existing medical disorders (diabetes, hypertension, autoimmune diseases, chronic kidney disease, and chronic obstructive pulmonary disease, etc.)…”
mentioning
confidence: 99%
“… 2 In a separate publication, Peltzer et al examined the incidence of AF and the correlation with outcomes amongst patients with severe respiratory distress syndrome, also in New York City. 6 In a cohort of 1,053 patients, 18.4% had AF or atrial flutter. Of these, 9.6% of cases involved new-onset disease.…”
Section: Covid-19 and Atrial Fibrillationmentioning
confidence: 99%